Multiple Switching Patterns for SHEPWM Inverters Using Differential Evolution Algorithms - Ayong Hiendro (Institute of Advanced Engineering and Science, 2011)
An investigation on multiple patterns for both odd and even number of switching angles in a three-phase selective harmonic elimination pulse width modulation (SHEPWM) inverter is presented. The switching patterns are examined and classified on the basis of the harmonic performance of the waveforms output from the inverter. Differential evolution algorithms are employed to calculate the optimum switching angles. Selected cases are verified experimentally by a digital signal processor-based hardware implementation. The experimental results show that all types of the patterns offer low harmonic distortions on the inverter output after filtering. However, one type gives better harmonic performance is identified.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.101